The Factors Influencing Tokopedia's Purchase Intention: Application of Theory of Planned Behavior - Mario Hugo Glenn Jacoub; Haryo Priambodo Adinegoro (iBuss Management, 2022)
The shift from buying and selling goods from mortar and brick stores towards the internet has made shopping online an integral part of society. In Indonesia society, there is a major e- commerce platform by the name Tokopedia, which leads the online shopping activity on a national scale. However, it is still unclear what drives the purchase intention in the case of Tokopedia, therefore the researchers wish to understand the factors that would influence the purchase intention in Tokopedia. This research used Tang (2021) theory of planned behavior framework, analyzing the relationship between the individual attitude, subjective norm, and perceived behavioral control from the theory of planned behavior towards purchase intention in the case of Tokopedia. The research focuses on Tokopedia users which are in Indonesia, through a quantitative approach using simple random sampling, with online questionnaires for obtaining the data, 110 respondents were analyzed using PLS-SEM and bootstrapping method. The findings show that subjective norm and perceived behavioral control does affect purchase intention, however attitude does not.Keywords: Attitude, Perceived behavioral control, Subjective norm, Purchase intention